The Kinship Terms of the Uzbek and Karakalpak Nations (On the example of Uzbek dialects of Karakalpakstan) (Eurasian Scientific Herald, 2022)
This article compares the terms of kinship found in the speech of the Turkic peoples living in the territory of Karakalpakstan with Kipchak and Oghuz dialects. Words that occur in a particular group of each nation are shown on the basis of examples that they do not occur in another nation or its dialects.